2011
DOI: 10.1111/j.1468-3083.2011.04363.x
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia as a rare but distinct manifestation of pemphigus vulgaris

Abstract: In PV, the combination of anti-desmoglein autoantibody-mediated acantholysis in conjunction with secondary factors, such as inflammatory changes due to infection, may cause weakening of hair follicle anchorage resulting in hair loss and alopecic patches. This unusual clinical phenotype should alert physicians to PV as a potential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 20 publications
(29 reference statements)
1
29
0
1
Order By: Relevance
“…[4] Indeed, also in our patient, a skin swab cultured S. aureus , which was also cultured in one previous pemphigus vulgaris and alopecia case. [4]…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…[4] Indeed, also in our patient, a skin swab cultured S. aureus , which was also cultured in one previous pemphigus vulgaris and alopecia case. [4]…”
Section: Discussionmentioning
confidence: 56%
“…It has been suggested that antibody-mediated acantholysis between outer root sheath keratinocytes is responsible for the hair loss, but the fact that alopecia is not seen in most pemphigus patients implies that an additional secondary factor is needed for hair-loss induction. [4] One such proposed factor is secondary infection, which was evident in all cases of a recently published case series where skin swabs were taken. [4] Indeed, also in our patient, a skin swab cultured S. aureus , which was also cultured in one previous pemphigus vulgaris and alopecia case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 We acknowledge that we incorrectly stated that alopecia is frequently observed in pemphigus patients in our manuscript, which should have read infrequently, as indicated in the cited reference. 4 In their letter, Drs. Grando and Pittelkow claim that our results, in conjunction with previous animal studies, failed to substantiate that Dsg3 is the principal desmosomal cadherin that holds keratinocytes together.…”
Section: From the Department Of Immunology Duke University Medical Cmentioning
confidence: 96%